Recovery From Covid-19 Is A Valuable Experience: A Systematic Review - Dadik Dwi Fata Suparda; Ninuk Dian Kurniawati; Andri Setiya Wahyudi (Poltekita : Jurnal Ilmu Kesehatan, 2023)
COVID-19 is a global health problem that affects the physiological and psychological of patients even though they have passed through an acute period. The recovery process from COVID-19 is also still limited. This study aims to examine the physiological and psychological health problems of COVID-19 survivors. Methods: A systematic search was conducted through five databases (Proquest, Science Direct, Web of Science, PubMed, and Scopus) using  qualitative research criteria with interviews and limited article searches from January 2020 to January 2022. The data search used the keywords recovery, rehabilitation, experience, COVID-19 or coronavirus, qualitative. Dissemination and review of the use of the JBI Guidelines to assess research quality. Systematic analysis using the Prisma checklist guide. Title, abstract, full text, and methodology used to access the location. Researchers perform data tabulation and narrative analysis of the findings. Results: Seven studies met the inclusion criteria. The results of the study are divided into two themes in the recovery of COVID-19. Factors that affect physiological (n=2), psychological (n=3) and affect both (n=2). An average of 176 participants from all studies discussed physiological and psychological factors in COVID-19 recovery. Results: Physiological problems in the form of fatigue, shortness of breath, sleep disturbances, decreased appetite, and cough. Psychological problems in the form of fear, depression, anxiety, and stress. Conclusion: Survivors of COVID-19 have different physiological and psychological health problems in recovery or rehabilitation, so they are need support from other people or health workers and a good environment for a prosperous life.